ANALISIS PENGARUH CAMEL TERHADAP KINERJA PERUSAHAAN PERBANKAN YANG GO PUBLIK - Wahyu Widati Listyorini (Dinamika Akuntansi Keuangan dan Perbankan, 2012)
The purpose of this research is to analysis the influence of Camel (CAR,PPAP,DER,BOPO,LDR) toward Performance of Banking Companies  in Indonesia This research use secondary data, with the source of data from Bank Indonesia and Indonesia Capital Market Directory publication. Technical sampling used purposive sampling and total sample is 85 firm with the 86 observation sample. The analysis use regression least square –OLS. The result of Capital Adequacy Ratio/CAR and Loan to Deposit Ratio are significant positive influence to the Return On Asset/ROA, but PPAP have positive and not significant influence to Return On Asset, Debt to Equity Ratio/DER have positive significant to Return On Asset , BOPO have positive and not significant to Return On Asset. Key word:   capital adequacy ratio, ppap, debt to equity ratio, bopo, loan to deposit  ratio, return to asset